Has the COVID-19 Pandemic Led to Changes in the Tasks of the Primary Care Workforce? An International Survey among General Practices in 38 Countries (PRICOV-19) - Groenewegen, Peter; Van Poel, Esther; Spreeuwenberg, Peter; Batenburg, Ronald; Mallen, Christian; Murauskiene, Liubove; Peris, Antoni; Petre, Benoit; Schaubroeck, Emmily; Stark, Stefanie; Sigurdsson, Emil L.; Tatsioni, Athina; et al. (International Journal of Environmental Research and Public Health, 2022)
The COVID-19 pandemic has had a large and varying impact on primary care. This paper studies changes in the tasks of general practitioners (GPs) and associated staff during the COVID-19 pandemic. Data from the PRICOV-19 study of 5093 GPs in 38 countries were used. We constructed a scale for task changes and performed multilevel analyses. The scale was reliable at both GP and country level. Clustering of task changes at country level was considerable (25%). During the pandemic, staff members were more involved in giving information and recommendations to patients contacting the practice by phone, and they were more involved in triage. GPs took on additional responsibilities and were more involved in reaching out to patients. Problems due to staff absence, when dealt with internally, were related to more task changes. Task changes were larger in practices employing a wider range of professional groups. Whilst GPs were happy with the task changes in practices with more changes, they also felt the need for further training. A higher-than-average proportion of elderly people and people with a chronic condition in the practice were related to task changes. The number of infections in a country during the first wave of the pandemic was related to task changes. Other characteristics at country level were not associated with task changes. Future research on the sustainability of task changes after the pandemic is needed.
CRIS-Team Scopus Importer:2022-12-09
Keywords: COVID-19; general practice; general practitioners; international comparison; PRICOV-19; primary care workforce; primary health care; quality of care; task changes

Recruitment, data collection, participation rate, and representativeness of the international cross-sectional PRICOV-19 study across 38 countries - Tatsioni, Athina; Groenewegen, Peter; Van Poel, Esther; Vafeidou, Kyriaki; Assenova, Radost; Hoffmann, Kathryn; Schaubroeck, Emmily; Stark, Stefanie; Tkachenko, Victoria; Willems, Sara (BMC Primary Care, 2023)
Background: Recruitment for surveys has been a great challenge, especially in general practice. Methods: Here, we reported recruitment strategies, data collection, participation rates (PR) and representativeness of the PRICOV-19 study, an international comparative, cross-sectional, online survey among general practices (GP practices) in 37 European countries and Israel. Results: Nine (24%) countries reported a published invitation; 19 (50%) had direct contact with all GPs/GP practices; 19 (50%) contacted a sample of GPs /GP practices; and 7 (18%) used another invitation strategy. The median participation rate was 22% (IQR = 10%, 28%). Multiple invitation strategies (P-value 0.93) and multiple strategies to increase PR (P-value 0.64) were not correlated with the PR. GP practices in (semi-) rural areas, GP practices serving more than 10,000 patients, and group practices were over-represented (P-value < 0.001). There was no significant correlation between the PR and strength of the primary care (PC) system [Spearman’s r 0.13, 95% CI (-0.24, 0.46); P-value 0.49]; the COVID-19 morbidity [Spearman’s r 0.19, 95% CI (-0.14, 0.49); P-value 0.24], or COVID-19 mortality [Spearman’s r 0.19, 95% CI (-0.02, 0.58); P-value 0.06] during the three months before country-specific study commencement. Conclusion: Our main contribution here was to describe the survey recruitment and representativeness of PRICOV-19, an important and novel study.
CRIS-Team Scopus Importer:2024-12-16
Keywords: COVID-19; Family medicine; PRICOV-19 study; Primary health care; Quality of care; Recruitment; Representativeness

“What else to say?”-Primary health care in times of COVID-19 from the perspective of German general practitioners: An exploratory analysis of the open text field in the PRICOV-19 study - Stark, Stefanie; Kluge, Marie; Schaubroeck, Emmily; Werner, Felix; van Poel, Esther; Willems, Sara; Roos, Marco; Kühlein, Thomas; Burggraf, Larissa (PLoS ONE, 2023)
Background The international collaboration study PRICOV-19 -Primary Health Care in times of COVID-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on the subjective perceptions of general practitioners on primary health care and the impact of political measures during the second wave of the COVID-19 pandemic. Within this survey, the “open text field” of the questionnaire was utilised remarkably frequently and extensively by the respondents. It became clear that the content that was named needed to be analysed in an exploratory manner. Accordingly, this paper addresses the following question: What preoccupies general practitioners in Germany during COVID-19 that we have not yet asked them enough? Methods The data collection took place throughout Germany from 01.02.2021 to 28.02.2021with a quantitative online questionnaire consisting of 53 items arranged across six topics as well as an “open text field” for further comments. The questionnaire's open text field was analysed following the premises of the qualitative content analysis. Results The topics discussed by the respondents were: insufficient support from health policies, not being prioritised and involved in the vaccination strategy, feeling insufficient prepared, that infrastructural changes and financial concerns threatened the practice, and perceiving the own role as important, as well as that health policies affected the wellbeing of the respondents. One of the main points was the way general practitioners were not sufficiently acknowledged for their contribution to ensuring high-quality care during the pandemic. Discussion German general practitioners perceived their work and role as highly relevant during the COVID-19 pandemic. In controversy with their perception, they described political conditions in which they were the ones who contributed significantly to the fight against the pandemic but were not given enough recognition.
CRIS-Team Scopus Importer:2023-03-31